Greece : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2009)
This Selected Issues paper provides updates on Greece's financial stability framework. The paper highlights that the Bank of Greece (BoG) has strengthened the financial stability framework over recent years. In addition to the liquidity provided by the euro system through its regular refinancing operations and standing facilities, the BoG can provide emergency liquidity assistance (ELA) to financial institutions. In response to the global financial crisis, the authorities have assisted bank capital and funding. A manual has been developed to monitor financial stability and spell out contingency plans for the management of crises.